The Nepali Communist Movement and People’s Multiparty Democracy - Pokhrel, Ishwar (State, Society and Development: PMPD Perspectives, 2024)
Madan Bhandari postulated People’s Multiparty Democracy (PMPD) to bolster both the Nepali Communist Movement and the International Communist Movement. As the global experiment with Marxism under one-party communist rule and the Soviet model of socialism collapsed, and the partyless Panchayat regime in Nepal became unpopular, Madan Bhandari fused classical Marxism, Leninism, and New Democracy, liberal democracy with the unique situation of Nepal to establish the foundational concept of PMPD. This article retraces the developmental trajectory of PMPD in conjunction with the evolving Communist Movement in Nepal. It examines PMPD’s development from its initial adoption at the Fifth National General Convention of the Communist Party of Nepal (Unified Marxist-Leninist) through the party’s subsequent General Conventions. In this light, this paper reveals that PMPD emerged not only as a central principle for the party’s vision of socio[1]economic transformation and political strategy but also provided insights for other political parties and movements. Furthermore, this paper explores the potential of PMPD to address citizens’ needs exceptions, and core national interests. The future of Nepal’s communist movement depends on its adherence to democratic principles and popular consent. Nepali communists must remain competitive to retain the revolution’s achievements, and strategies must align with current realities. Finally, an excessive focus on democratization at the expense of revolutionary change and socio-economic transformation goals may undermine the progress of the communist movement in Nepal.